Development of an Android-based Humidity and Air Temperature Monitoring Application for the Greenhouse of Gapoktan Lembang Agri - Al-Fadhlih, Muhammad Ilyas; Amarullah, Luthfy Fahlevi; Purba, Adrico Alexander; Hartawan, Liman; Rakhmat, Galih Ashari (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Unpredictable climate change poses significant challenges for farmers at Gapoktan Lembang Agri in maintaining sustainable production. To support quick and precise decision-making, a mobile-based monitoring system has been developed, enabling real-time monitoring of greenhouse temperature and humidity through an Android application. This system utilizes IoT sensors to measure environmental parameters, with the collected data transmitted to a server via the internet and displayed directly in the application. The application is designed using Jetpack Compose to ensure a responsive and user-friendly interface, even for users with limited technical knowledge. Firebase is employed as a real-time data management platform to guarantee data accuracy and processing speed. Key features include live monitoring, access to historical data, and data export capabilities for further analysis. The system has been successfully implemented and tested in the greenhouse of Gapoktan Lembang Agri, demonstrating its ability to provide real-time monitoring and accurate data. Feedback from users indicates ease of use and the application's effectiveness in helping farmers respond proactively to environmental changes.